Designing a solar collector using f-chart method for domestic hot water in Malaysia - Abdul Rahman, Fatiha (2018)
The solar energy system converts solar energy into useful energy.The performance system depends on the weather that changes over period of time.This make it difficult to analyse accurately the solar system performance by simply referring to the short-term or average weather conditions.To overcome this problem,researchers often do experiments and software such as TRNSYS,Simulink,MATLAB and more.In this study,the f-chart method was used to predict the solar collector system.The f-chart method is one of the empirical frameworks that use metric standards to characterize the long-term performance of the solar system.Nowadays,many researchers use the f-chart method because of its simple analysis formula.In addition,the f-chart method is the easiest method to determine the size of the solar collector.The f-chart method considered value of x and y throughout the year to determine the annual fraction of the load supplied by solar energy.A total of 3 varied sizes of solar collectors were used in this study.Residential areas in Bangi have been selected in this study to design hot water heating systems using solar energy and data for ambient temperature and average solar radiation in 2013 have been used to make this study possible.After doing this study,the load given by the solar collector for 3 varied sizes is not the same as 0.38,0.66 and 0.84.This shows that 0.84 is the highest and shows that 84% of the load is supplied by solar energy.The monthly average domestic heating in Malaysia is 1.22 GJ.Meanwhile,the total domestic heating temperature in Malysia is 14.66 GJ.